Field notes contributed by Lee A. Schoenewe, spring 1996 - Schoenewe, Lee A.et al (1996)
Spring report of birds found in northwest Iowa contributed by Lee A. Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed